Improving the Mechanical Properties of Epoxy by Adding Sub-micron Cantaloupe Peel Fibers - Rand B. Lutfi; Widad H. Jassim (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2023)
The use of bio-fruit waste has more attention in recent years because of the low cost of bio-fibers and the protection of the environment. In this study, the epoxy was reinforced with fruit residues (cantaloupe peel powder) in proportions (1%, 2%, 3%, 4%, 5%, 7.5%, and 10% by weight) as results of mechanical tests such as impact, hardness, flexural and compression.